Episodes Coherence in the Moving Image Text - Ngamsa, John (International Journal of Arts, Languages, Linguistics and Literary Studies, 2024)
This paper titled "Episodes Coherence in the Moving Image Text" explores the concept of coherence in film narratives and the moving image text. It highlights the theoretical perspectives presented by Cummings, Greenberg, and Kelly (2017) and Baumgarten (2008) in understanding episode coherence in films. Drawing on these theoretical frameworks, the paper reviews how filmmakers employ semiotic features and pictures to achieve coherence within and between episodes in film narratives. Examples of these features and pictures are presented to illustrate their effectiveness in enhancing the overall narrative structure and coherence. The theories put forth as reviewed provide insights into the role of episodic coherence in shaping viewers’ perception and understanding of a typical film. This paper also highlights the importance of narrative structure and its impact on audience engagement in tandem with other patterns of semiotic features which emphasize the visual storytelling elements and how they contribute to coherence in film narratives. The findings of this study underscore the significance of carefully crafting semiotic features and pictures to maintain coherence within episodes, as well as creating a smooth transition between them. The narrative structure and visual elements play crucial role in ensuring that viewers can follow and understand the story being presented on screen. Finally, based on the analysis conducted, further recommends that future research could explore the impact of different semiotic features and visual techniques on audience perception of coherence in film narratives. Additionally, comparative studies between different genres or time periods could provide valuable insights into the evolving nature of episode coherence in the moving image text.